2022
DOI: 10.26803/ijlter.21.1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coworker and Supervisor Support on Stress among Malaysian School Teachers during the COVID-19 Pandemic

Abstract: In the current COVID-19 crisis, teaching is difficult. The demands from students, parents, the government, and school administrators may be overwhelming. Many Malaysian teachers are experiencing growing mental strain, and they are reluctant to seek help due to social stigma. This quantitative study explored the impact of coworker and supervisor support on stress among primary and secondary school teachers in Malaysia. In addition, the study examined the spill-over impact of stress on teachers’ turnover intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In addition, social support also buffers the negative effects of job demands; it moderates the relationship between stressors and well-being, and other workrelated outcomes (Bakker and Demerouti, 2007). In the work and organisational psychology literature, the positive impact of organisational support and general social support in the work environment on workers' well-being, motivation, and performance is well established (Latham and Pinder, 2005;Ciobanu et al, 2019), including for the teacher population during the COVID-19 pandemic (Prado-Gascó et al, 2020;Khan et al, 2022;Ong and Sulaiman Khan, 2022;Stang-Rabrig et al, 2022;Sudibjo and Manihuruk, 2022). We thus also expected that:…”
Section: The Present Studymentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, social support also buffers the negative effects of job demands; it moderates the relationship between stressors and well-being, and other workrelated outcomes (Bakker and Demerouti, 2007). In the work and organisational psychology literature, the positive impact of organisational support and general social support in the work environment on workers' well-being, motivation, and performance is well established (Latham and Pinder, 2005;Ciobanu et al, 2019), including for the teacher population during the COVID-19 pandemic (Prado-Gascó et al, 2020;Khan et al, 2022;Ong and Sulaiman Khan, 2022;Stang-Rabrig et al, 2022;Sudibjo and Manihuruk, 2022). We thus also expected that:…”
Section: The Present Studymentioning
confidence: 96%
“…In extant studies, there job demands were found as leading to unfavourable outcomes for teachers and other workers such as increased efforts, cognitive irritation, informational overload, negative emotions, psychological distress, a lack of motivation, and work effectiveness decline (Day et al, 2010(Day et al, , 2012Almpanis and Joseph-Richard, 2022;Kasprzak and Mudło-Głagolska, 2022;Gualano et al, 2023;Scheel et al, 2023). Meanwhile, research shows that job resources include pre-existing ICT skills and self-efficacy in distant teaching that facilitate the move to distance learning and prevent burnout (Westphal et al, 2022), previous experience with distance learning (van der Spoel et al, 2020;Pozo et al, 2022) and with teaching in general (Cheptea et al, 2021), support received by the colleagues and school management (either material, organisational, or emotional;Prado-Gascó et al, 2020;Awada et al, 2021;Khan et al, 2022;Ong and Sulaiman Khan, 2022;Stang-Rabrig et al, 2022;Sudibjo and Manihuruk, 2022), and psychological characteristics such as resilience, positive selfperceptions (e.g., competence), and emotional regulation (Restubog et al, 2020;Manuti et al, 2022;Pečjak and Pirc, 2022;Scheibe et al, 2022).…”
Section: Distance Teaching Within the Framework Of Job Demands-resour...mentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that burnout has been a phenomenon among teachers in Malaysia for a long time and things get worst during the era of COVID-19. This is due to the overwhelming demands from students, parents, the government, and school administrators during the difficult time (Ong & Khan, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The reviews carried out by Holguín (2021) discovered that the physical, mental, and social health of educators had been impacted by the COVID-19 pandemic. In a study conducted by Ong and Khan (2022) among 250 Malaysian school teachers, they revealed that teachers showed high turnover intention amidst the pandemic, which obliquely exemplified high dissatisfaction and poor well-being. Moreover, because of the poor enrolment of students in certain private higher institutions, pay cuts, and other related deductions were also imposed on teaching staff (Fong, 2021;Siti, 2020).…”
Section: Introductionmentioning
confidence: 99%